(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2013)
Social responsibility, despite its long existence and evolution, has had a limited understanding and recently has tried to rethink and address ways. This study aimed to know and understand the level of understanding that teachers have a university in the region Laja - Bajío, in the state of Guanajuato, Mexico. We interviewed 45 teachers who chose to answer the questions, from a universe of 60 present at the time of the interviews within the institution, a total of 164 teachers, 51 full professors and 96 lecturers (including teachers sporting and cultural activities) respondents belong to the Engineering Energy, Agro Engineering, Manufacturing Engineering Technology, Robotics Engineering and the Licenciatura in Administration and Management of SMEs, about the impact of the University in terms of social responsibility. Teachers identified, based on ISO 26000 environmental dimensions, human rights and community involvement, as important elements of social responsibility, the dimension of governance was slightly outlined in speeches and references not identified dimensions of labor practices, fair operating practices and consumer business. While the results are partial of a broader research and presents only the perception of the teachers interviewed, outlining an approach allows not conclusive, the way how to construct the concept of social responsibility of universities.